Medical Treatment of Graves’ Orbitopathy - Salvi, M.; Campi, I. (Hormone and Metabolic Research, 2015)
The medical treatment of Graves’ orbitopathy (GO) is usually reserved to moderate to severe disease. Steroids have been widely employed and possess anti-inflammatory activity, but about 20–30% of patients are not responsive and about 20% present with disease recurrence. Immunosuppressive therapy alternative to corticosteroids may target the different antigens involved in pathogenic mechanisms of GO. Some have already been employed in clinical studies and showed interesting results, although the lack of randomized and controlled trials suggests caution for their use in clinical practice. Potential targets for therapy in GO are the TSH receptor and the IGF-1 receptor on the fibroblasts, inflammatory cytokines, B and T cells. Most promising results are obtained by interacting with the PIK3/mTORC1 signaling cascades for adipogenesis and the anti-IGF-1R with the monoclonal antibody teprotumumab. A recent open study has shown that tocilizumab, an anti-sIL-6R antibody, inactivates GO. Consistent reports on the efficacy of rituximab have recently been challenged by randomized controlled trials. Clinical practice will greatly benefit from the use of disease modifying agents in GO, as compared to steroids, currently standard treatment for GO. Among these, rituximab may be useful, especially in patients resistant to steroid or with contraindications to steroids. However, larger randomized controlled trials are needed for definitive data on the potential disease-modifying role of rituximab in GO. Direct targeting of the orbital fibroblast via immunosuppression or nonimmunosuppressive drugs is emerging as a promising alternative.
Keywords: Graves’ orbitopathy; cytokines; TSH receptor; IGF-1 receptor; rituximab; B cells